Resource Wealth, Innovation and Growth in the Global Economy - Pietro F. Peretto; Simone Valente (ETH Zurich, CER-ETH - Center of Economic Research, 2010)
We analyze the relative growth performance of open economies in a two-country model where different endowments of labor and a natural resource generate asymmetric trade. A resource-rich economy trades resource-based intermediates for final manufacturing goods produced by a resource-poor economy. Productivity growth in both countries is driven by endogenous innovations. The effects of a sudden increase in the resource endowment depend crucially on the elasticity of substitution between resources and labor in interme- diates' production. Under substitution (complementarity), the resource boom generates higher (lower) resource income, lower (higher) employment in the resource-intensive sector, higher (lower) knowledge creation and faster (slower) growth in the resource-rich economy. The resource-poor economy adjusts to the shock by raising (reducing) the relative wage, and experiences a positive (negative) growth effect that is exclusively due to trade.
Keywords: E10; F43; L16; O31; O40; 330; Endogenous Growth; Endogenous Technological Change; Natural Resources; International Trade; Endogenes Wachstumsmodell; Natürliche Ressourcen; Substitutionselastizität; Offene Volkswirtschaft; Zwei-Länder-Modell; Theorie